2020
DOI: 10.1007/s11239-020-02226-0
|View full text |Cite
|
Sign up to set email alerts
|

High D dimers and low global fibrinolysis coexist in COVID19 patients: what is going on in there?

Abstract: Backgroud COVID-19 coagulopathy linked to increased D-dimer levels has been associated with high mortality (Fei Z et al. in Clinical course and risk factors for mortality of adult inpatients with COVID-19 in Wuhan, China: a retrospective cohort study. Lancet (London, England) 395(10229):1054-62, 2020). While D-dimer is accepted as a disseminated intravascular coagulation marker, rotational thromboelastometry (ROTEM) also detects fibrinolysis (Wright FL et al. in Fibrinolysis shutdown correlates to thromboembol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(136 citation statements)
references
References 23 publications
9
122
1
4
Order By: Relevance
“…No abnormal fibrinolytic activity was noted. In the same way, nineteen ICU COVID-19 patients were recruited by Ibanez et al and demonstrated clot firmness above the normal range in the EXTEM and FIBTEM tests, while clot lysis was decreased [ 18 ]. Clot firmness and clot lysis were assessed against the normal range and reported levels in the healthy controls, respectively.…”
Section: Evaluation Of Coagulopathy By Viscoelastic Methods In Sevmentioning
confidence: 99%
See 2 more Smart Citations
“…No abnormal fibrinolytic activity was noted. In the same way, nineteen ICU COVID-19 patients were recruited by Ibanez et al and demonstrated clot firmness above the normal range in the EXTEM and FIBTEM tests, while clot lysis was decreased [ 18 ]. Clot firmness and clot lysis were assessed against the normal range and reported levels in the healthy controls, respectively.…”
Section: Evaluation Of Coagulopathy By Viscoelastic Methods In Sevmentioning
confidence: 99%
“…However, a correlation between ROTEM parameters and severity illness scores has not been reported [ 18 ]. It should be also pointed out that, in most cases, ICU COVID-19 patients have longer or normal CT/R values [ 12 , 13 , 17 , 18 , 19 ]. This is the only parameter not supporting the procoagulant profile of critically ill COVID-19 patients.…”
Section: Evaluation Of Coagulopathy By Viscoelastic Methods In Sevmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 1 st to 30 th April 2020, 41 acutely ill patients admitted to internal medicine department wards underwent a CTPA because respiratory deterioration after admission, and represent the study population. The median (IRQ) age of the cohort was 71.7 (63-76) years, 30 (73%) were females, the median days (IRQ) since onset of symptoms to hospitalization was 8 (4-12) and the median days (IRQ) since onset of symptoms to CTPA was 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). By the end of May 2020 in-hospital mortality of the cohort was 4.88%, with 2 patients still hospitalized and 90% already discharged.…”
Section: Resultsmentioning
confidence: 99%
“…Although data from different studies indicate that the incidence of venous thromboembolism (VTE) in COVID-19 patients is higher than that seen in similarly ill hospitalized non COVID-19 subjects, the exact prevalence of APE in COVID-19 patients is not known, and the diagnostic value of D-dimer in subjects with acute SARS-CoV-2 infection is not clear [5]. In effect, the increase in mortality associated with elevated D-dimer values in these patients may re ect an increased rate of APE, but it also could be a manifestation of disseminated intravascular coagulation or simply a higher level of systemic in ammation [9]. Therefore, data on the value of D-dimer and other clinical and biochemical markers for the diagnosis of VTE in subjects hospitalized for COVID-19 may improve the diagnostic and therapeutic approach to this disease.…”
Section: Introductionmentioning
confidence: 99%